Hubungan Pengetahuan Ibu dengan Kepatuhan Pemberian Imunisasi Measles Rubella (MR 1) pada Bayi di Wilayah Kerja Puskesmas Saritani - Ni Kadek Puryanti (Pusat Riset dan Inovasi Nasional, 2026)
Measles Rubella (MR) immunization plays a crucial role in protecting children from measles and rubella, both of which can lead to severe disability or even death. The effectiveness of this immunization program largely depends on mothers’ level of knowledge and their consistency in ensuring their children receive vaccines on schedule. This study aimed to examine the relationship between maternal knowledge and adherence to the Measles Rubella (MR 1) immunization among infants in the Saritani Public Health Center area. A quantitative approach with a cross-sectional design was applied. The study population included 168 mothers with infants aged 9–12 months, and 62 of them were selected as respondents through convenience sampling. Data were gathered using a structured questionnaire measuring mothers’ knowledge and adherence, adapted from the instrument developed by Rosada Uli Simangunsong (2021). The data were analyzed using the Chi-Square test in Microsoft Excel with a 0.05 significance threshold. The results revealed that most mothers had a moderate level of knowledge (61.29%) and low adherence (58.06%). The Chi-Square analysis produced a p-value of 0.028 (p < 0.05), demonstrating a significant association between knowledge and adherence to MR immunization. These findings suggest that maternal knowledge plays an important role in determining immunization adherence. Strengthening health education, enhancing the involvement of health workers and Posyandu cadres, and developing innovative immunization reminder systems are necessary to increase MR immunization coverage in the community.